Cherry necrotic rusty mottle and Cherry green ring mottle viruses in Czech cherry germplasm - Josef ŠPAK; Jaroslava PŘIBYLOVÁ; Dana ŠAFÁŘOVÁ; Ondřej LENZ; Igor KOLONIUK; Milan NAVRÁTIL; Jana FRÁNOVÁ; Vlastimila ŠPAKOVÁ; František PAPRŠTEIN (Plant Protection Science, 2017)
Using reverse transcription polymerase chain reaction, 160 sweet and sour cherry trees from a germplasm collection, orchards, and wild trees in the Czech Republic were screened for the presence of Cherry necrotic rusty mottle virus (CNRMV) and Cherry green ring mottle virus (CGRMV). The viruses were detected exclusively in sweet cherry trees in the germplasm collection, with CNRMV determined in two trees and CGRMV in four trees. Using next-generation sequencing, nearly complete genomic sequences (complete ORFs) were obtained for one CNRMV and three CGRMV isolates. Their relatedness to GenBank sequences of isolates from different countries together with negative results from screening outside of the germplasm collection suggests that the viruses had been imported with accessions.